(untitled) (International Journal of Physiology, 2020)
Aim and Objective: The purpose of this study is to evaluate results of memory scores in normal healthy adult. Brain areas involved in memory such as the hippocampus, the amygdala, the striatum, or the mammillary bodies are thought to be involved in specific types of memory. Pranayama is to control the body function by controlling our breath Materials and Method: This study was conducted in the yoga center on 62 subjects. Subjects were trained for breath holding yoga training. they performed for total of 30 minutes duration daily. At the end of four week the subjects were examined by WECHSLER memory scale. Observations: The results showed increase in scores of all types of test DSF, DSB, and all are highly significant P<0.001. Results: All the scores of Wechsler memory scales are highly significant after pranayama. Conclusion: The repeated measure ANOVA analysis revealed a significant increase in memory. This study concludes that yoga enhances numerical data retrieval mostly as a result of left-brain activation.